(untitled) (REVISTA NODO, 2025)
This practical teaching inquiry explores the emerging dynamics between human creativity and artificial intelligence in the training of art directors, based on pedagogical experiences developed across three formative levels with graphic design students at Fundación Universitaria Los Libertadores. The reflection analyzes how the relationship with generative AI tools evolves throughout the formative sequence: workshop, project, and studio. The didactic approaches implemented at each level are documented, including exercises in “prompt engineering” and “post-generative intervention”. The results show significant transformations in students’ understanding of creative processes, developing metacognitive skills about their own process when confronted with automated systems. The study identifies emerging patterns of creative hybridization that generate greater value, mainly the cultural contextualization of generic outputs. This inquiry offers an approach to a methodological framework for art direction educators seeking to integrate these technologies without sacrificing the development of aesthetic judgment and critical thinking, using conceptual pedagogy and its proposed didactic sequence as a foundation.